The mRNA Expression Of Inducible Nitric Oxide Synthase In Keloid Using Tocotrienol-Rich Fraction In Primary Human Epidermal Keratinocytes And Primary Human Dermal Fibroblast Cultures - Yusuf, Siti Mahirah (2012)
Keloid is characterized by excess collagen deposition that can damage healthy tissue. With the widespread use of Vitamin E- tocopherols based product and the discovery of tocotrienol (T3) potential to treat various skin injuries; there are possibilities of tocotrienol-rich fraction (TRF) to intercede normal, hypertrophic, or keloid scarring during the inflammatory process. However, there is a lack of scientific evidence to validate the efficacy and the therapies of TRF in scar prevention. Thus, this study was carried out to evaluate the beneficial effects of TRF in wound healing and its possible stimulation towards mRNA expression of inducible nitric oxide synthase (iNOS) in keloid human skin keratinocytes and fibroblasts.